2020
DOI: 10.1017/pasa.2020.1
|View full text |Cite
|
Sign up to set email alerts
|

The development of non-coherent passive radar techniques for space situational awareness with the Murchison Widefield Array

Abstract: The number of active and non active satellites in Earth orbit has dramatically increased in recent decades, requiring the development of novel surveillance techniques to monitor and track them. In this paper, we build upon previous non-coherent passive radar space surveillance demonstrations undertaken using the Murchison Widefield Array (MWA). We develop the concept of the Dynamic Signal to Noise Ratio Spectrum (DSNRS) in order to isolate signals of interest (reflections of FM transmissions of objects in orbi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
(63 reference statements)
3
13
1
Order By: Relevance
“…All of the detected objects in this work (except three CubeSats and one MiniSat) were detected within the theoretically predicted parameter space. Two of the CubeSats (DUCHIFAT-1 and UKUBE-1) were detected due to out-of band transmissions in the FM band (as previously observed by Zhang et al 2018 andPrabu et al 2020b) and the other CubeSat and MiniSat were detected through FM reflections. Some satellites such as the ISS and Hubble Space Telescope (HST) were also detected outside the MWA's primary beam due to their large RCS.…”
Section: False Positivessupporting
confidence: 63%
See 3 more Smart Citations
“…All of the detected objects in this work (except three CubeSats and one MiniSat) were detected within the theoretically predicted parameter space. Two of the CubeSats (DUCHIFAT-1 and UKUBE-1) were detected due to out-of band transmissions in the FM band (as previously observed by Zhang et al 2018 andPrabu et al 2020b) and the other CubeSat and MiniSat were detected through FM reflections. Some satellites such as the ISS and Hubble Space Telescope (HST) were also detected outside the MWA's primary beam due to their large RCS.…”
Section: False Positivessupporting
confidence: 63%
“…Previously, Prabu et al (2020b) demonstrated the so-called dynamic signal to noise ratio spectrum (DSNRS) technique, detecting signals from satellites/debris, either via FM reflections or downlink transmissions, and differentiates them from other types of radio frequency interference (RFI) entering the detection system (the MWA). This previous work utilised the results of Zhang et al (2018) to select a small set of MWA observations known to contain signals reflected from satellites.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At these frequencies, as well as ducted propagation from distant transmitters, multi-path reception of RFI is expected due to reflections of objects within the environment. For example, reflections of aircraft (Wilensky et al 2020), ionised meteor trails (Zhang et al 2018), and satellites (Prabu et al 2020b;Zhang et al 2018;Tingay et al 2013b) are expected. Such signals are ubiquitous and have been studied in detail for other low frequency radio telescopes such as the Owens Valley Long Wavelength Array (Monroe 2018).…”
Section: Introductionmentioning
confidence: 99%